PREVALENCE OF GASTROINTESTINAL PARASITES IN BUFFALO AND COW CALVES IN RURAL AREAS OF TOBA TEK SINGH, PAKISTAN - Bilal; M.Q; A. Hameed; T. Ahmad (Journal of Animal and Plant Sciences, 2009)
The present study was conducted on 160 calves (80 of each buffalo and cow). The results indicated that 75 % buffalo and 56.25% cow calves were positive for worm infestation. The highest prevalence of nematodes was recorded followed by mixed infection and cestodes, and no calf was found positive for trematodes. Buffalo and cow calves between 1 to 6 months of age exhibited highest prevalence (86.67, 69.05 %) compared to the age group of 7 to 12 months (60, 42.10 %). Calves on grazing were heavily infected (83.33 % buffalo calves, 75 % cow calves) than those of stall fed (70 % buffalo calves, 46.16 % cow calves). Buffalo male calves were more affected (88.38 %) than female calves (59.46 %) where as, the same was for cow calves. Maximum farmers in the study area were totally ignorant about the recommended calf related management techniques and following the traditional practices. Calf mortality up to 60 % was found in the study area and high worm infestation was one of the leading factors along with the non adoption of prophylactic measures.
Keywords: Prevalence; endo-parasites; cow calves; buffalo calves; field conditions.